Hubungan antara Kecemasan dalam Belajar dengan Motivasi Belajar Siswa - Yanti, Supri; Erlamsyah, Erlamsyah; Zikra, Zikra; Ardi, Zadrian (Konselor, 2013)
This study departs from the anxiety in students 'learning and students' motivation in learning. The purpose of this study were to examine the relationship of anxiety in learning with motivation to learn. The study was descriptive correlational. Results showed that there was no significant relationship between anxiety in learning and motivation to learn. Means that the higher the anxiety study, the higher the students' motivation.